The effects of combined black pepper extract and yogurt on histology of mice digestive organs - Mutiati, Enni; Inayah, Nurul; Putri, Kanza Nabila (JPBIO (Jurnal Pendidikan Biologi), 2026)
Black pepper contains piperine, which can irritate the digestive organs. Therefore, this study combined black pepper with yogurt containing probiotic bacteria, which are known to play a role in maintaining the balance of microbiota and digestive tract health. The objective of this study was to analyze the histopathology and histomorphometry of the digestive organs, particularly the stomach and small intestine, of mice (Mus musculus) after administration of a combination of black pepper extract and yogurt. The present study was conceptualized as an experimental study, employing a completely randomized design (CRD), encompassing five distinct treatments (distilled water, yogurt, a black pepper extract at a dose of 25, 50, 75 mg/kg BB, and yogurt. The results demonstrated that the thickness of the stomach wall in all treatment groups remained within the normal range. Treatment P2 demonstrated optimal outcomes, exhibiting a thickness of each layer of the stomach wall that ranged between the minimum and maximum values. In the small intestine, all histomorphometric parameters exhibited values that remained within the normal range. The conclusion of this research is combination did not result in an increase in gastric acid secretion and did not induce irritation to the gastric and small intestinal mucosa of mice.